2020
DOI: 10.5897/ajb2020.17152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis among soybean genotypes using SSR markers in Uganda

Abstract: The assessment of genetic diversity among improved crop germplasm can facilitate the expansion of the genetic base for crop improvement in breeding program. However, little effort has been made to assess the level of genetic relatedness among released varieties and elite soybean [Glycine max (L.) Merr.] genotypes. The objective of this study was to determine the degree of genetic diversity that exists among released and elite soybean genotypes in Uganda. In this study, 21 polymorphic simple sequence repeat (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…PIC value and genetic diversity were fond to be positively correlated [51,73,74]. This is consistent with the findings of this study, the marker Satt063, with the lowest genetic diversity value of 90%, has a PIC value of 0.89 (Table 6).…”
Section: Molecular Analysissupporting
confidence: 91%
“…PIC value and genetic diversity were fond to be positively correlated [51,73,74]. This is consistent with the findings of this study, the marker Satt063, with the lowest genetic diversity value of 90%, has a PIC value of 0.89 (Table 6).…”
Section: Molecular Analysissupporting
confidence: 91%
“…The amplification process was carried out in a thermocycler (G Storm, UK), with the following conditions: Initial denaturation took place at 95 °C for 5 minutes, then there were 35 cycles of 95 °C for 2 minutes, annealing temperature at 53 to 58 °C for 30 seconds, extension at 72 °C for 40 seconds, and final extension at 72 °C for 5 minutes (Clever 2019).…”
Section: Simple Sequence Repeats (Ssr) Analysismentioning
confidence: 99%
“…Gel electrophoresis was used to separate the PCR products on 2% metaphor agarose gel (Lonza Bioscience, Singapore), stained with ethidium bromide stain (10 µl /100 µl of 1X TAE buffer) with a constant supply of 100 volts for 1 hour with a size standard of 100 bp for the ladder (Clever, 2019). Using a Bio-Doc-ItTM Imaging System, gel pictures were captured (Biotium, USA).…”
Section: Simple Sequence Repeats (Ssr) Analysismentioning
confidence: 99%
“…Studies have proven that Soybean varieties with appreciable yield performance are needed to sustain the production but their improvement has been slowed down by the low genetic diversity (Clever et al, 2020;Jo et al, 2021). Soybean is a predominantly self-pollinate crop (Chiari et al, 2005;Zhao et al, 2018) and has been in relating more to its genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Clever et al, (2022) and Obua et al, on soybean genetic diversity reported less diversity in the raw breeding soybean materials. Hence, they recommended enlarging the genetic diversity of soybean collection to create a genetic variation that is necessary to cope with the dynamics of biotic and abiotic stresses that affect soybean production in Uganda (Clever et al, 2020;. But in those studies, few accessions were involved and guring the availability or importation of new soybean accessions as part of the solution, this study sought to the genetic diversity and population structure of a set of 282 soybean lines from Zimbabwe, Taiwan, the USA, and Uganda using the Diversity Array Technology Sequencing (DArT-Seq).…”
Section: Introductionmentioning
confidence: 99%